Answer:
Multiply 1st equation by 3
Step-by-step explanation:
To eliminate -3y, we must multiply the 1st equation by such a number that the -y becomes -3y. This can be done by multiplying the 1st equation by 3.
If you would like more tutoring in math or other subjects for FREE, check out growthinyouth.org.
Answer:
B.$120
Step-by-step explanation:
find 8 on the bottom, and go up until you find the dot. then look to the left to see what number matches it on the left side.
Answer:
Step-by-step explanation:
No solutions....means the lines are parallel...means ur 2 equations have to have the same slope but different y intercepts
y = 2x + 4 and y = 2x + 3
========================
Infinite solutions...means u have the same line
y = 2x + 4 and 2y = 4x + 8....notice how if u reduce the 2nd one by dividing everything by 2 u get y = 2x + 4...same line
========================
1 solution....means ur equations will have different slopes and different y intercepts.
y = 2x + 4 and y = 4x + 2
now, u can pick which one u want :)
Answer: f(0) = 6.
Explanation:
Ther ordered pairs are: (x,y) or (x, f(x) )
So, (1,0) means that f(1) = 0 which denies the fourth choice.
(-10,2) means that f(-10) = 2 which denies the first choice
(0,6) means that f(0) = 6, which is the third choice. So, that is the true equation.
Answer:
x = z/(6πy)
Step-by-step explanation:
Divide by the coefficient of x.
z/(6πy) = 6πxy/(6πy)
z/(6πy) = x